Desenvolvimento de nanocompósitos de polianilina/TiO2 e compósitos de polianilina/NaAlH4 para armazenamento de hidrogênio - Moreira, Bruna Rodrigues (Universidade Federal de São Carlos, 2013)
Hydrogen is considered a clean and versatile energy vector that can be used for many applications, having water as the major product of combustion, it a great potential to be an alternative to fossil fuels. However, the challenge for the establishment of hydrogen technology to be used widely and safely is hydrogen storage. In this work, it was studied the preparation of composites and nanocomposites using the polyaniline (Pani) as polymer matrix in order to obtain a new material for hydrogen storage. In situ Pani/Titanium dioxide (TiO2) nanocomposites with 10 or 30 wt% of TiO2 were prepared using two dopants: hydrochloric acid and docecylbenzenesulfonic acid (DBSA). Both polyaniline and TiO2 were synthesized. Pani/sodium alanate (NaAlH4) composites with 30 or 50wt% of NaAlH4 were prepared from dispersions in toluene. These composites were also doped with 2 mole% of TiO2 in order to decrease the sorption temperature of hydrogen. Two drying processes were studied: Spray Drying process and filtration followed by drying in a vacuum oven. Morphological characterization of the composites and nanocomposites showed a good dispersion of the filler in the polymeric matrix, in addition, microspheres of NaAlH4 encapsulated by Pani were obtained using the spray dryer process. Hydrogen sorption analyses were carried out for pure Pani-DBSA and for the composites with 50wt% of sodium alanate and 2 mole% of TiO2 obtained for the two different drying processes. From these analyses, the composites showed sorption of 0.60% H2, higher than that obtained for the pure polymer (0.42%). These results show evidence that the proposed composites may be used for hydrogen storage.
Development of polyaniline/TiO2 nanocomposites and polyaniline/NaAlH4 composites for hidrogen storage
Keywords: Compósitos; Polianilina; Hidrogênio - armazenamento; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA